DESIGN AND IMPLEMENTATION OF IMMIGRATION LEGAL INFORMATION RELATED TO THE APPLICATION FLOW FOR ADDITIONAL NAMES ON PASSPORTS AT THE IMMIGRATION OFFICE BELAKANG PADANG - Yudi Kornelis; Alif Firdausa (ConCEPt - Conference on Community Engagement Project, 2022)
This practical work program aims to assist the Immigration Office Class II TPI Belakang Padang in providing information on immigration law related to the flow of applications for adding names to passports. As addressed to the public, especially for prospective applicants, with appropriate procedures based on the provisions of applicable regulations. The process of collecting data needed in the design of this project was through field observations and interviews with several authorized immigration officials. The final result of this practical work is in the form of a video slideshow and poster containing a flowchart regarding the flow of the application for adding a name to the passport, which is printed and uploaded through the official Instagram account of the Class II Immigration Office of TPI Belakang Padang.